2015
DOI: 10.1002/acr.22690
|View full text |Cite
|
Sign up to set email alerts
|

Within‐Day Variability of Fatigue and Pain Among African Americans and Non‐Hispanic Whites With Osteoarthritis of the Knee

Abstract: Objective Fatigue is common among persons with osteoarthritis (OA), but little is known about racial/ethnic differences in the prevalence, correlates, or dynamics of fatigue in OA. This research therefore used experience sampling methodology (ESM) to examine fatigue and pain at global and momentary levels among African Americans and non-Hispanic whites with OA. Methods Thirty-nine African Americans and 81 non-Hispanic whites with physician-diagnosed knee OA completed a baseline interview and an ESM protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…Our sample was predominantly white. Within the context of evidence for racial/ethnic differences in pain and fatigue experiences in people living with OA, 5,45,54 as well as impacts on the sleep−fatigue relationships, 21,59 our findings are not generalizable to diverse populations. Further research that specifically recruits a broader demographic is required to examine the potential role that racial, ethnic, and culture differences play in the sleep−pain and sleep−fatigue relationships.…”
Section: Discussionmentioning
confidence: 59%
“…Our sample was predominantly white. Within the context of evidence for racial/ethnic differences in pain and fatigue experiences in people living with OA, 5,45,54 as well as impacts on the sleep−fatigue relationships, 21,59 our findings are not generalizable to diverse populations. Further research that specifically recruits a broader demographic is required to examine the potential role that racial, ethnic, and culture differences play in the sleep−pain and sleep−fatigue relationships.…”
Section: Discussionmentioning
confidence: 59%
“…These findings highlight the importance of fatigue variability [21] and the potential dynamic day-to-day nature of different fatigue dimensions in the knee OA population. Interestingly these carry-over effects observed for fatigue dimensions were potentially informative, perhaps indicating that effective management of different fatigue dimensions could lead to subsequent decrements in fatigue across days with positive carry over effects perhaps lasting longer for mental fatigue.…”
Section: Fatigue Dimensions Between Daysmentioning
confidence: 74%
“…Observational studies using intensive longitudinal methods and ecological momentary assessment (EMA), defined as real-time measurements of experiences or behaviours in a free-living environment [18], have higher ecological validity than traditional longitudinal designs and can better capture participant's daily life [19,20]. Considering the complexity of the relationship between fatigue and PA and their variability over short time periods [12,21,22], an intensive longitudinal assessment approach provides the possibility to study short-term dynamics (i.e., within day or across days) between different PA metrics and fatigue dimensions in knee OA [19]. Importantly, we do not know when a PA measure at one time point may has its maximal effect on fatigue variables at a later time, nor do we know if temporal precedence (fatigue dimensions precede different PA patterns or vice versa) exists between fatigue dimensions and different PA metrics in free-living in knee OA.…”
Section: Oamentioning
confidence: 99%
“…Several in vivo microlongitudinal studies, using daily or weekly diary approaches, have similarly demonstrated that variation in persistent pain is associated in predictable ways with contemporaneous and lagged fluctuation in mood states [9][10][11][12]. Similar patterns have been documented on even shorter, within-day time frames using experience sampling methods [13][14][15].…”
Section: Introductionmentioning
confidence: 73%